the Analisis Semiotika Penggunaan Bahasa Jawa pada Berita Utama Koran Jawa Pos Radar Blitar (Edisi Januari-Februari 2024) - Raysenda, Meylvin Damar; Meifilina, Andiwi; Kusumawijayanti, Anita Reta (Universitas Islam Balitar, 2024)
Javanese is a regional language commonly used by the Javanese people for interactions. The minimal use of Javanese Krama, this language is still in use today. The media company Jawa Pos Radar Blitar combines Indonesian and Javanese languages to disseminate information. This study aims to examine the use of Javanese in the main news articles of Jawa Pos Radar Blitar, focusing on the types and meanings. Researchers use qualitative research method to uncover data facts. The analysis results of using Semiotic Roland Barthes theory indicate there are three types of Javanese language in the January-February 2024 edition, namely ngoko, madya, and krama. Javanese Krama is not in Jawa Pos Radar Blitar. Ngoko is the most frequently used, with 13 words have positive meanings, while madya has only 3 words with negative. Positive meanings are defined as clear and singular, whilenegative meanings are ambiguous and have multiple interpretations.